Effect of oral vitamin K prophylaxis on prothrombine time and activated partial thromboplastin time: a randomized controlled comparison with an intramuscular vitamin K in infants - V. Lily Limantara; Sudaryat S.; I. B. Mudita; W. Retayasa; M. Kardana (Indonesian Pediatric Society, 2007)
Background Low plasma concentration of vitamin K in thenewborn accounts for serious bleeding in the neonatal period andearly infancy. The aim of prophylactic vitamin K is to preventbleeding. Oral prophylaxis is preferable to intramuscular (IM)administration because oral administration is less expensive andless traumatic.Objective To compare oral vs. intramuscular vitamin K onprothrombine time (PT) and activated partial thromboplastin time(APTT) during the first 60 days of life.Methods We randomized newborn infants to either receive oralvitamin K 2 mg at birth and repeated at 7 and 30 days of life orthe 1 mg intramuscular vitamin K. PT and APTT were monitoredat 0, 15, and 45 days of age. Independent t-test, repeatedmeasurement, and regression analysis were used for statisticalanalyses and comparison of the results.Results Fifty infants were assigned into the oral group and 50 tothe IM group. All participants completed 60 days of study. BothPT and APTT decreased after administration of oral or IM vitaminK, and the values did not differ significantly at any time pointand through the period of investigation. Using regression analysisit was shown that only vitamin K administration was correlatedwith PT and APTT with P value were 0.044 and 0.036,respectively. During 60 days of study, there was no hemorrhagicdiathesis in both groups.Conclusions Through the first 60 days of life, 3 doses of oralvitamin K maintain hemostasis by decreasing PT and APTT ininfants at values equal to those achieved by the intramuscularpreparation. Diathesis hemorrhagic event did not occur in bothgroups.